A revision of the South African katydid genus Austrodontura Fontana & Buzzetti (Orthoptera: Tettigoniidae: Phaneropterinae) - Naskrecki, Piotr; Bazelet, Corinna S. (Zootaxa, 2011)
The South African genus Austrodontura Fontana & Buzzetti of brachypterous katydids is revised. A. capensis (Walker, 1869) is redescribed and A. castletoni sp. n. from the Eastern Cape Province is described, A. raggei Fontanta & Buzzetti is considered a junior synonym of A. capensis. Acoustic behavior of A. castletoni is described.